Comicism as an object of study in linguistics - Islomova Madina Askarovna (Genius Journals, 2024)
In this article, we consider the field of comics as a research object of linguistics, how the unique features and structures of the medium provide rich opportunities for linguistic analysis and research, and by in-depth study of the nuances of speech, we will make it a research object of linguistics. we will study the importance of comics as an act
Keywords: methods; linguistics; comics; sarcasm